China: A World Leader in Graduation Rates - Marioulas, Julian (International Higher Education, 2017)
Graduation rates at higher education institutions in China are among the highest worldwide. Faculty and administration avoid weeding out low-performing students for a plethora of reasons. This can have an adverse effect on student performance, especially at colleges with low entry requirements. It also enables corruption in the admissions process. The author argues that graduation, being almost guaranteed, is acting as an impediment to the further development of Chinese universities.